BAP1-Altered Malignant Pleural Mesothelioma: Outcomes With Chemotherapy, Immune Check-Point Inhibitors and Poly(ADP-Ribose) Polymerase Inhibitors - Dudnik, Elizabeth; Bar, Jair; Moore, Assaf; Gottfried, Teodor; Moskovitz, Mor; Dudnik, Julia; Shochat, Tzippy; Allen, Aaron M.; Zer, Alona; Rotem, Ofer; Peled, Nir; Urban, Damien (Frontiers in Oncology, 2021)
Objectives Little is known regarding the outcomes of systemic treatments in BAP1-altered malignant pleural mesothelioma (MPM). Materials and Methods Forty five patients with MPM [group A: eight MPM patients with BAP1 inactivating mutation/copy number loss (FoundationOne® CDx/TEMPUSxT), selected from the electronic databases of four Israeli cancer centers (ICC); group B: 37 consecutive (years 2016–2018) MPM patients selected from the electronic databases of two ICC—of those six patients without a BAP1 alteration (group B1) and 31 patients not tested for BAP1 (group B2)] were analyzed for ORR, PFS (mRECIST), and OS with 1st-line platinum/pemetrexed+/−antiangiogenic drug (CT, n-28), immune check-point inhibitors (ICPi, n-16) and poly (ADP-ribose) polymerase inhibitors (PARPi, n-4). OS since diagnosis (OSDx) was assessed. Results There were no differences in ORR or mPFS with CT between the groups: ORR-50% vs. 47% vs. 50% vs. 47% (p>0.9), mPFS-9.1mo (95% CI, 1.2–16.1) vs. 9.2mo (95% CI, 2.9–13.3) vs. 7.2mo (95% CI, 2.3-NR) vs. 10.9mo (95% CI, 2.9–20.3) (p>0.8) in groups A, B, B1, and B2, respectively. There were no differences in ORR or mPFS with ICPi between the groups: ORR-0% vs. 27% vs. 33% vs. 25% (p>0.2), mPFS-2.5mo (95% CI, 1.4–3.7) vs. 3.0mo (95% CI, 1.3–10.5) vs. 2.0mo (95% CI, 1.9-NR) vs. 4.5mo (95% CI, 0.3–10.5) (p>0.3) in groups A, B, B1, and B2, respectively. In group A, no responses were seen with PARPi; mPFS with PARPi was 1.8mo (95% CI, 1.8-NR). OSDx was 98.3mo (95% CI, 9.7–98.3) vs. 19.4mo (95% CI, 9.7–47.3) vs. 18.8mo (95% CI, 8.5-NR) vs. 19.5mo (95% CI, 8.3–82.2) in groups A, B, B1, and B2, respectively (p>0.3). Conclusions BAP1-altered MPM, as compared to non-selected MPM, is characterized by similar efficacy of CT and ICPi. Numerically longer OS in BAP1-altered MPM may reflect favorable tumor biology. No responses were observed with PARPi.